Contabilidade rural no apoio do gerenciamento do agronegócio pelos pecuaristas do município de Paraíso Do Tocantins- TO - Braga, João Marcos Gomes (Universidade Federal do Tocantins, 2021)
Agribusiness in the Brazilian economic context is the sector of the economy that has become important over the years, due to its potential for income generation in the region of the municipality of Paraíso do Tocantins -TO, in particular the livestock activity. Due to this economic evolution, Rural Accounting emerges as a branch of Accounting Science, with the purpose of providing information related to the assets of rural entities. In this sense, it is convenient to verify the importance of Rural Accounting in supporting the management of agribusiness by ranchers in the municipality of Paraíso do Tocantins - TO. Exploratory in nature, using a bibliographic survey and field study, with a qualitative approach, the research was aimed at livestock farmers living in the region of the municipality in question, and for data collection, interviews were conducted on the spot following a structured question script, applied to 10 respondents. The results achieved through the analysis of the data obtained reveal that, most of the ranchers are unaware of Rural Accounting and its usefulness as a tool to support the management of the activity developed, from this perspective it shows the lack of applicability of this science.